HEART score performance in Asian and Caucasian patients presenting to the emergency department with suspected acute coronary syndrome. Issue 7 (1st October 2018) - de Hoog, Vince C; Lim, Swee Han; Bank, Ingrid E M; Gijsberts, Crystel M; Ibrahim, Irwani B; Kuan, Win Sen; Ooi, Shirley B S; Chua, Terrance S J; Tai, E Shyong; Gao, Fei; Pasterkamp, Gerard; den Ruijter, Hester M; et al.
Abstract: Background: The HEART score is a simple and effective tool to predict short-term major adverse cardiovascular events in patients suspected of acute coronary syndrome. Patients are assigned to three risk categories using History, ECG, Age, Risk factors and Troponin (HEART). The purpose is early rule out and discharge is considered safe for patients in the low risk category. Its performance in patients of Asian ethnicity is unknown. We evaluated the performance of the HEART score in patients of Caucasian, Chinese, Indian and Malay ethnicity. Methods: The HEART score was assessed retrospectively in 3456 patients presenting to the emergency department with suspected acute coronary syndrome (1791 Caucasians, 1059 Chinese, 344 Indians, 262 Malays), assigning them into three risk categories. Results: The incidence of major adverse cardiovascular events within six weeks after presentation was similar between the ethnic groups. A smaller proportion of Caucasians was in the low risk category compared with Asians (Caucasians 35.8%, Chinese 43.5%, Indians 45.3%, Malays 44.7%, p <0.001). The negative predictive value of a low HEART score was comparable across the ethnic groups, but lower than previously reported (Caucasians 95.3%, Chinese 95.0%, Indians 96.2%, Malays 96.6%). Also the c-statistic for the HEART score was not significantly different between the groups. Conclusions: These results show that the overall performance of the HEART score is equal among Caucasian and Asian ethnic groups. The event rate in the low risk group, however, was higher than reported in previous studies, which queries the safety of early discharge of patients in the low risk category.